The Predictive value of serum glutathione S-transferase (GST-π), P-glycoprotein (PGP), P53, Ki-67 and breast cancer :Systematic review and meta-analysis: serum markers and breast cancer - zhang, nuan (Journal of Medical Biochemistry, 2025)
0